Predicting Sediment Yield in Barakar River Valley - Bundela, D.S. (Journal of Soil and Water Conservation, 2022)
In this Paper, an attempt is made to develop a dimensionally homogeneous and statistically optimal model for the prediction of sediment yield from small watersheds in Barakar river valley. Eleven watersheds are chosen for model development and two watersheds for model validation. Rainfall, topography soil attributes, land use and land treatment attributes are included in the model. It is observed that model involving land treatment attribute results in higher correlation coefficient and F-value. The validation result shows that model is able to predict the average annual sediment production rate within the reasonable limits of the observed sediment production rate.